ANTIOXIDANT ACTIVITY AND HEPATOPROTECTIVE POTENTIAL OF BALANITES ROXBURGHII FRUITS - T, RAJANANDA SWAMY; B, GANGA RAO; P, Haritha (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objectives: The objective of the present study was to evaluate antioxidant activity and hepatoprotective potential of a hydroalcoholic extract of Balanites roxburghii (BR) fruits. Methods: Extraction was performed by triple maceration using ethanol:water as a solvent. The extracts were vaporated using rotavapor. Then antioxidant capacities were tested using superoxide, hydroxyl, and 1,1-diphenyl-2-picrylhydrazyl (DPPH) radicals. Determination of hepatoprotective model was performed by thiocetamide induced liver models. Results: The hydroalcoholic extract of BR fruits produced a dose-dependent percentage inhibition on tested free radicals, i.e., superoxide anion (50% inhibition concentrations [IC50] value 190.50 Î¼g/ml), hydroxyl radical (IC50 value 266.30 Î¼g/ml), and DPPH radical (IC50 value 175 Î¼g/ml). After treatment with silymarin and hydroalcoholic extract of BR in respective groups, they had showed good protection against thioacetamide induced liver toxicity. Conclusion: The results of the present investigation clearly indicate the free radical scavenging activity and hepatoprotective potential of a hydroalcoholic extract of BR fruits and this activity is comparable with that of the standard drugs ascorbic acid and silymarin. Keywords: Balanites roxburghii, Antioxidant activity, Hepatoprotective activity, Ascorbic acid.